Household heat pump adoption and user behaviours: a systematic review of drivers and barriers - Lynn A. de Jager; Liesbeth Claassen; Geeske Scholz; Emile J.L. Chappin; Anne van Bruggen (International Journal of Sustainable Energy)
This systematic literature review synthesises the literature on socio-psychological drivers and barriers to heat pump adoption and efficient use in households, drawing from the 16 research articles available. The review reveals mixed findings: variables were found influential in some studies but not in others. In addition to financial considerations, negative expectations regarding comfort and performance also hinder adoption. The literature on user behaviours suggests that comfort, knowledge, and home characteristics influence how heat pumps are operated, including temperature settings, heating area, and ventilation behaviour. A key research gap is the insufficient study of variables relating to the individual, such as psychological and socio-demographic factors. Based on the findings, we recommend public awareness campaigns to emphasise non-financial benefits of heat pumps, particularly comfort, which users often experience as an advantage. To optimise user behaviour, we recommend offering technical support services, simplifying system interfaces, and providing actionable feedback information on energy consumption.